PROFILE CLASSES AS A TOOL FOR THE DEVELOPMENT OF THE EDUCATIONAL ENVIRONMENT FOR TRAINING WORKERS AND ENGINEERING PERSONNEL FOR ADVANCED TECHNOLOGY - E. Z. Yagubov; S. Yu. Dubikovsky (Высшее образование в России)
The article considers the interaction of general and higher education with partner companies in formation of profile classes as a factor of successful training of workers and engineering personnel. The authors analyze the experience of interaction with LLC “Gazprom transgaz Ukhta” in the implementation of the project “Gazprom-class”.